2010
DOI: 10.1007/s10661-010-1696-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay as monitoring system for lead phytoremediation through Crinum asiaticum L.

Abstract: Toxicity of lead in soil is well documented and established. Phytoremediation has gained attention as a cheap, easily applicable, and eco-friendly clean-up technology. Chemical methods are used to assess exact levels and type of pollutants but heavy metal content in soil can also be evaluated indirectly by estimation of phytotoxicity levels using bioassays. Plant bioassays through fast germinating cereals can indicate not only the level of pollution and its effects on growth and survival but also the progress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…Some studies were consistent with our results indicating that barley might be a promising phytoremediation crop (Varun et al, 2011;Masu et al, 2012 andGonzález et al, 2017); furthermore, certain genotypes of barley might be used in phytoextraction (Masu et al, 2012); however, adaptability and stability issues need to be considered in this case. On the other hand, other studies suggested that other plant species might be more appropriate for phytoremediation, e.g.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some studies were consistent with our results indicating that barley might be a promising phytoremediation crop (Varun et al, 2011;Masu et al, 2012 andGonzález et al, 2017); furthermore, certain genotypes of barley might be used in phytoextraction (Masu et al, 2012); however, adaptability and stability issues need to be considered in this case. On the other hand, other studies suggested that other plant species might be more appropriate for phytoremediation, e.g.…”
Section: Discussionsupporting
confidence: 90%
“…in grain cereals; however, it is paramount to control accumulation of these micronutrients lower than toxicity levels by inhibiting their excess translocation to grains (Zhao & McGrath, 2009). Barley is a promising candidate as phytoremedial crop because of the strong correlation between its shoots growth and reducing heavy metals in soil (Varun et al, 2011). It can be exploited in phytoremediation of Cr, Cu and Fe; in addition, it has the ability to hyperaccumulate heavy metals in roots (Masu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many native, well adapted plants have been investigated and even used for heavy metal bioindicatoring and phytoremedial purposes including lemongrass and other wild grasses, vetiver, Sesbania, Avena, Crotalaria, Crinum asiaticum, Typha latifolia and Calotropis procera etc. [31][32][33][34][35]. Phytoremediation employing indigenous species can be an ecologically viable option for sustainable and cost-effective management.…”
Section: Phytosociological Studiesmentioning
confidence: 99%
“…Many native, well adapted plants have been investigated and even used for heavy metal bioindicatoring and phytoremedial purposes including lemongrass and other wild grasses, vetiver, Sesbania, Avena, Crotalaria, Crinum asiaticum, Typha latifolia and Calotropis procera etc. [31][32][33][34][35]28]. Native wild species are also important to remediate soils in context of the studied area due to a remark (April, 2006) of the Supreme Court prohibiting the cultivation of plants requiring fertilizers and pesticides along the Yamuna.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the soil is naturally high in a particular metal, native plants often become adapted over time to the locally elevated levels so in the case of native flora and soils, metal toxicity issues, mostly, do not arise. Avena, Crotalaria, Crinum asiaticum and Calotropis procera, lemongrass, and other wild grasses have been reported for heavy metal bioindicatoring and phytoremedial purposes (Uraguchi et al 2006;D'Souza et al 2010;Varun et al 2011). Allowing native species to remediate soils is an attractive proposition since a plant community comparable to that existing in the vicinity can be established.…”
Section: Introductionmentioning
confidence: 99%